Entrepreneurship Education in SMK Amanah Bangsa, Cikarang: ‘Starting-Up a Business is not that Hard’ - Genoveva Genoveva; Maria Jacinta Arquisola; Cindy Maydita Srianisha; Antonius Whisnu Perdana Widiputra (President University, 2019)
The government's attention to vocational graduates has recently become a hot issue and various programs have been carried out by the government to improve the quality of vocational graduates, therefore they can compete. However, the BPS data in 2018 shows that the number of unemployed graduates from vocational school (SMK) is the highest, namely 11.24%, while Senior High School (SMA) is 7.95% and Junior High School (SMP) is 4.80%. Based on the problem, Study Program of Management, Faculty of Business, President University implemented a community service program that supports government policy, namely by providing Entrepreneurship Education to students of Amanah Bangsa Informatics Vocational School, Cikarang. With this entrepreneurship education, SMK graduates are expected to start a business as an alternative after graduating later. Entrepreneurship education is given in the form of seminars for Class XII students conducted by lecturers and students. In addition to providing lecture material on Entrepreneurship, students who have carried out business projects also share their experiences while opening a business, doing business until business liquidation as part of Entrepreneurship Course. The point is that students want to convey that starting a business is easy and has many challenges that are very suitable for millennials, and can apply all our abilities. The event was closed by giving a memento to the Vocational School and certificates to the participants.